2012
DOI: 10.1111/j.1365-2966.2012.20622.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating incoherent dedispersion

Abstract: Incoherent dedispersion is a computationally intensive problem that appears frequently in pulsar and transient astronomy. For current and future transient pipelines, dedispersion can dominate the total execution time, meaning its computational speed acts as a constraint on the quality and quantity of science results. It is thus critical that the algorithm be able to take advantage of trends in commodity computing hardware. With this goal in mind, we present analysis of the 'direct', 'tree' and 'sub-band' dedis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
128
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 17 publications
0
128
1
1
Order By: Relevance
“…The complex voltage output for each tied-array beam-in the form of 200 Nyquist-sampled, dual-polarization subbands of 195 kHz each-was processed using GPU-accelerated software to perform coherent dedispersion and channelization with CDMT ) at steps of 1 pc cm −3 between dispersion measures (DMs) of 0.5 and 79.5 pc cm −3 . The resulting coherent filterbanks, sampled at 81.92 μs and 48.83 kHz in time and frequency, were dedispersed using the DEDISP library (Barsdell et al 2012). The dedispersed time series were searched for periodic signals using frequency domain acceleration searching (tools from PRESTO; Ransom 2001; Ransom et al 2002).…”
Section: Radiomentioning
confidence: 99%
“…The complex voltage output for each tied-array beam-in the form of 200 Nyquist-sampled, dual-polarization subbands of 195 kHz each-was processed using GPU-accelerated software to perform coherent dedispersion and channelization with CDMT ) at steps of 1 pc cm −3 between dispersion measures (DMs) of 0.5 and 79.5 pc cm −3 . The resulting coherent filterbanks, sampled at 81.92 μs and 48.83 kHz in time and frequency, were dedispersed using the DEDISP library (Barsdell et al 2012). The dedispersed time series were searched for periodic signals using frequency domain acceleration searching (tools from PRESTO; Ransom 2001; Ransom et al 2002).…”
Section: Radiomentioning
confidence: 99%
“…9 In Table 24 of Dewdney et al (2013), it is shown that the data processing for a pulsar survey with SKA1-mid is dominated by the acceleration search processing load of nearly 10 Peta operations per second; 10 times the processing power offered by the Einstein@Home network as of January 2013: http://einstein.phys.uwm.edu/ 10 Following the SKA1-mid survey parameters outlined in Table 24 of Dewdney et al (2013), and correcting for a jerk of ± 0.2 m s −3 (a value that could be observed in known compact significant progress in speeding up various aspects of pulsar search code has been made in recent years, primarily through the use of GPU technology (see e.g. Barsdell et al 2010;Magro et al 2011;Armour et al 2012;Barsdell et al 2012, Luo 2013 ). In the following sections our investigation is limited to searches utilizing the constant acceleration approximation only.…”
Section: Acceleration Searches and Computational Considerationsmentioning
confidence: 99%
“…A few 10 4 trial of dispersion measures are required, and a computing power of 0.1 Petaflops. In addition, the de-dispersion is very I/O intensive (Barsdell et al 2012). …”
Section: Timing Of Pulsarsmentioning
confidence: 99%